Google compute engine - Cohen, Marc; Hurley, Kathryn; Newson, Paul (O'Reilly Media, 2015)
Learn how to run large-scale, data-intensive workloads with Compute Engine, Google's cloud platform. Written by Google engineers, this tutorial walks you through the details of this Infrastructure as a Service by showing you how to develop a project with it from beginning to end.